The five languages of apology : how to experience healing in all your relationships - Chapman, Gary D., 1938-; Thomas, Jennifer, 1969- (Chicago : Northfield Pub., 2006)
In this book, you will lern how to recognize your own primary apology language while speaking the languages ot those you love. Understanding and applying the five languages of apology will greatly enhance all of your relationships.
Why apologize? -- Expressing regret : "I am sorry." -- Accepting responsibility : "I was wrong." -- Making restitution : "What can I do to make it right?" -- Genuinely repenting : "I'll try not to do that again." -- Requesting forgiveness : "Will you please forgive me?" -- Discovering your primary apology language : "What do I expect most in an apology?" -- Apologizing is a choice -- Learning to forgive -- Learning to apologize in the family -- Teaching your child to apologize -- Apologizing in dating relationships -- Apologizing in the workplace -- Apologizing to yourself -- What if we all learned to apologize effectively?
Includes bibliographical references.
Keywords: Apologizing; Apologizing